THE EFFECT OF CHARACTER, CAPACITY, CAPITAL, COLLATERAL AND CONDITION OF ECONOMY ON GIVING CREDIT - Angga Hapsila; Ivalaina Astarina (JURNAL MANAJEMEN DAN BISNIS, 2020)
This research was conducted by the authors at PT Bank Rakyat Indonesia (Persero) Tbk Kerumutan Unit and Tri Mulia Jaya Unit. The research took place for 4 ( four ) months. Conducting this research is to determine the effect of Character, Capacity, Capital, Collateral, and Condition of Economy simultaneously on the Provision of Credit at PT. Bank Rakyat Indonesia (Persero) Tbk Kerumutan Unit and Tri Mulia Jaya Unit. This study uses primary data, the authors conducted data processing using multiple linear regression which processed it using SPSS (statistical package for social science) version 21 to get the output to conclude the results of this study. From the results of the study, it can be concluded that simultaneously there is a significant influence between Character, Capacity, Capital, Collateral, and Condition of Economy on the Provision of Credit. When viewed from the summary model table, then r, which means the correlation coefficient, shows that Character, Capacity, Capital, Collateral, and Condition of Economy have a moderate relationship to the Provision of Credit.